ANALISA PENGARUH KESIAPAN SUPPLY BATUBARA TERHADAP DEMURRAGE VESSEL, DI PT. INDOMINCO MANDIRI, BONTANG, KALIMANTAN TIMUR - Sakdillah Sakdillah (INFO-TEKNIK, 2016)
Demurrage is a form of compensation due to violation of the time of loading and unloading cargo and usually stated in the lease contract of cooperation. Demurrage can sometimes cause a loss in the seller because it will increase the total cost of transportation. In 2010 PT. Indominco Mandiri received a loss by the lack of supply of coal to reach the 11 million USD. The variable is used as an object of research is the supply of coal and the actual rate of replenishment ships, supply of coal which is ready to sell the supply of coal production has an influence on the actual rate of replenishment ships. Analysis conducted to find the relationship and influence in this study using the Pearson product moment correlation analysis. The data used is the average of the actual supply of coal and ship loading rate in a year. The steps in the research is to determine the hypothesis in sentence form and statistics and make a helper table. Once complete data correlation calculation, obtained r = 0.674 and the relatively strong, diterminan coefficient of 45.37%, in order to know the influence of the coal supply to the actual charging rate is significant.